Human stool from science and islam perspective and sunnah dietary practices [Najis (Tinja) manusia daripada perspektif sains dan islam serta amalan pemakanan sunnah] - Kashim M.I.A.M.; Hasim N.A.; Othaman R.; Khalid R.; Samsudin M.A.; Yahaya M.Z.; Manaf Z.A.; Amin L.; Zin D.M.M. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Islam is a religion that emphasizes human health including the human digestive system. The human stool (stool) discussed in this study is a human waste which is one of the way to look at human health. The objectives of this research were to study the physiochemical and characteristics of stool and its usefulness from the perspective of science while the diet used by Rasulullah SAW is been described from the Islam perspective. The research was conducted using descriptive literature review. It was found that the digestive system is a complicated system. The stools is made up of 75% of water and 25% of solid materials and the characteristics of stools such as form, color and odor can affect human health. From the Islam perspectives, color, odor and taste are the fundamental factors need to be emphasized during the process of stool’s cleansing especially before religious rituals begin. In addition, diet, exercise, age and gender are the factors that differentiate the type of human stool. In fact, this study also stated some of the alternatives that are currently used to manage stools in maintaining health and environmental protection. This study then examined the diet of sunnah’s foods called in the Qur’an and the hadith which is proven to be rich in fiber and nutritious especially for the human digestive system. Therefore, the stools from the perspective of science are capable in describing human health and the diet of sunnah’s food is very good for the human digestive system. © 2018 Penerbit Universiti Kebangsaan Malaysia.